Household income unequally affects genetic susceptibility to pulmonary diseases: evidence from bidirectional Mendelian randomization study - Xu, Hongfa; Deng, Hailian; Wu, Yueying; Yang, Yu; Zheng, Xifeng (Frontiers in Medicine, 2024)
Objectives: Previous observational studies have reported a close association between socioeconomic status and pulmonary disease-related morbidity. However, the inherent causal effects remain unclear. Therefore, this bidirectional Mendelian randomization (MR) study aimed to identify the causal relationship between household income and genetic susceptibility to pulmonary diseases.Methods: An MR study was conducted on a large cohort of European individuals, using publicly available genome-wide association study datasets using a random-effects inverse-variance weighting model as the main standard. Simultaneously, MR-Egger regression, weighted median, and maximum likelihood estimation were applied as supplements. Sensitivity analysis, comprising a heterogeneity test and horizontal pleiotropy test, was performed using the Cochran's Q, MR-Egger intercept, and MR-PRESSO tests to ensure the reliability of the conclusion.Results: A higher household income tended to lower the risk of genetic susceptibility to chronic obstructive pulmonary disease (COPD, OR: 0.497, 95% CI = 0.337-0.733, P<0.001), asthma (OR: 0.687, 95% CI = 0.540-0.876, P = 0.002), and lung cancer (OR: 0.569, 95% CI = 0.433-0.748, P<0.001), and further indicated potential causality with pneumonia (OR: 0.817; 95% CI = 0.686-0.972, P = 0.022). No association was evident with COVID-19 (OR: 0.934, 95% CI = 0.764-1.142, P = 0.507), tuberculosis (OR: 0.597, 95% CI = 0.512-1.189, P = 0.120), or bronchiectasis (OR: 0.680, 95% CI = 0.311-1.489, P = 0.400). Reverse MR analysis suggested no reverse causal relationship between pulmonary disease and household income status, while sensitivity analysis verified the reliability of the results.The results revealed that the population with a higher household income tended to have a lower risk of genetic susceptibility to COPD, asthma, and lung cancer.